The rural development: An approachfrom the new rurality (2015)
The rural development has been subject to different conceptual approximations, in fuction of the prevaling socio-spatial time. There stands out: the structuralism and the modernization which had influence from the 50´s to the mid 60´s, the dependence from the mid 60´s until the end of 70´s, the neoliberalism since the 80´s, the neostructuralism and the rural life strategies starting from the 90´s (1) and the territorial approach (2). The new rurality can be located on the life strategies approach and it has had a broad development and study in Latin America. Whit this orientaton is intented to understand the rural areas complexity and dynamics, which trancends its traditional conception as a producer and food supplier sector. This frame work is pertaining to study, due that the rural context, is the agrarian professional´s work place.Whit this review it is pretended to contribute to build the new rural scene concept, as a tool to analize the rural sector by compiling and analyzing the different authors contributions. The results indicate that this approach correspond to the rural population adaptation to the economic, social and cultural phenomena, recognizng the multidimensonality of rural areas, is a relevant approach to understand and to intervene in the rural development problems.